Ultrafast control of moiré pseudo‐electromagnetic field in homobilayer semiconductors - Zhai, Dawei; Yao, Wang (Natural sciences (Weinheim), 2022)
In long‐wavelength moiré patterns of homobilayer semiconductors, the layer pseudospin of electrons is subject to a sizable Zeeman field that is spatially modulated from the interlayer coupling in moiré. By interference of this spatial modulation with a homogeneous but dynamically tunable component from an out‐of‐plane electric field, we show that the spatial‐temporal profile of the overall Zeeman field therefore features a topological texture that can be controlled in an ultrafast timescale by a terahertz field or an interlayer bias. Such dynamical modulation leads to the emergence of an in‐plane electric field for low‐energy carriers, which is related to their real space Berry curvature—the moiré magnetic field—through Faraday's law of induction. These emergent electromagnetic fields, having opposite signs at the time reversal pair of valleys, can be exploited to manipulate valley and spin in the moiré landscape under the control of a bias pulse or terahertz irradiation. Key Points Temporal control of topological texture through the interference of spatial and temporal modulations. Emergent electromagnetic fields in nanoscale that can be manipulated in picosecond timescale. Pulsed spin and valley pseudospin current controlled by electrical bias or terahertz irradiation. Spatial‐temporal modulation of layer pseudospin in moiré of homobilayer semiconductors with bias pulse or terahertz irradiation generates ultrafast pseudo‐electromagnetic responses for valley‐spintronic applications.